Non-random trimer arrangement in Bacillus cereus ATCC 10987 chromosome - Huyen, Phan Thi; Luong, Nguyen Duc (Academia Journal of Biology, 2012)
Different from the linear chromosomes of eukaryotes, most chromosomes of bacteria are circular. In this paper, we investigated the arrangement of trimers in Bacillus cereus chromosome by recording physical positions of individual trimers along the single-stranded sequence of this chromosome in the 5’ to 3’ direction. Our very first finding was that numbers of individual trimers in this chromosome were very much not the same. In an attempt to find out how the trimers were arranged along the chromosome, we found that every trimer was distributed unevenly and throughout the chromosome. Each trimer was also found to distribute differently on each side of the origin of replication. In addition, the frequency of a trimer and that of its reverse complement, such as ATG and CAT, in the local regions of chromosome were always biased. Interestingly, however, the distribution of trimers in the sense and antisense sequences of chromosome exhibited an order in their arrangement, letting us to conclude that the trimer arrangement in the sense and antisense sequences shaped the codon usage of this bacterium at the chromosomal level.